New Instruments for Investment Support of Technology Sovereignty Projects - A. B. Sokolov; V. I. Filatov (Мир новой экономики)
The growth of restrictive measures against the Russian Federation in the context of the high import dependence of the national economy calls for special attention to be paid to the country’s achievement of technological sovereignty and the launching of a new sustainable investment cycle. This involves the task of dynamically increasing the creation of new medium- and high-technology industries, with a central role being given to the creation of a resource database of projects. Limited public budgets and the inaccessibility of external financial markets make it appropriate to consider domestic private and (or) resources as priority sources of financing debt, especially when the latter are not sufficiently involved in the investment process. In turn, it is unlikely to accumulate the funds of credit organizations and the business sector without the use of modern state support tools that would reduce the cost of capital for the implementation of investment projects and, thus, they redirected financial flows to the highest priority, albeit low-margin, of the real sector. Thus, the purpose of this article is to analyze new instruments of investment support of projects of ensuring technological sovereignty in the territory of the Russian Federation.